Means of the automated control of ecological parameters of petroleum derivatives - Turchyk, P. M.; Vasylkivskyi, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers the problem dealing with determination of the basic parameters of petroleum derivatives, which influence the state of environment during combustion of fuel in internal combustion engines. The principle of operation has been analyzed , block diagrams of means of the automated control for determination of general content of sulphur compounds and mechanical impurities of petroleum are suggested, possibilities of spectral analyzers for determination of octane value of petroleum derivatives according to spectra of their absorption, dispersion and transmission in infra-red area are described.